Assessment and Comparison of the Efficacy of Methotrexate, Prednisolone, Adalimumab, and Tocilizumab on Multipotency of Mesenchymal Stem Cells - Liu, Shuang; Kiyoi, Takeshi; Ishida, Marina; Mogi, Masaki (Frontiers in Pharmacology, 2020)
Mesenchymal stem cell (MSC)-based articular regeneration might be beneficial for both protecting and rebuilding cartilaginous tissues in the management of rheumatoid arthritis. However, it is unclear how current immunosuppressive strategies influence the multipotency of MSCs. The present study was undertaken to profile the direct effectiveness of major antirheumatic drugs including methotrexate, prednisolone, adalimumab, and tocilizumab on the multipotency of MSCs, with a special focus on chondrogenesis. The inhibitory effects of methotrexate on adipogenesis, osteogenesis, and chondrogenesis were observed to occur in a dose-dependent manner in an in vitro differentiation system. Prednisolone enhanced adipogenesis, but reduced alkaline phosphatase activity in osteoprogenitors and suppressed the formation of chondrospheroids. Adalimumab suppressed alkaline phosphatase activity, while tocilizumab diminished osteogenesis and chondrogenesis of MSCs in vitro. Chondrogenesis of antirheumatic drug-treated MSCs was also evaluated in vivo using a scaffolded spheroid-engrafted murine model. The biologics examined appeared to be relatively safe for cartilaginous formation, but methotrexate and prednisolone exhibited opposing influences on chondrogenesis. Taken together, these results reveal the direct efficacy of major antirheumatic agents on the multipotency of MSCs. Therefore, our findings suggest that optimization of medication protocols is further required for therapeutic approaches involving cartilaginous tissue engineering.